Silicone-based insulating material for battery module

By using sprayable thixotropic crosslinkable silicone composition, the problem of insufficient heat energy release in the combustion event of the battery module is solved, efficient thermal insulation protection is achieved, and economical and easy to apply.

CN119654735APending Publication Date: 2025-03-18WACKER CHEMIE AG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380053991.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-26
Filing Date
2023-10-09
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing battery modules are difficult to effectively limit the release of heat energy during combustion events, resulting in insufficient thermal insulation between the vehicle and the environment, and commonly used flame retardant materials are difficult to apply due to high viscosity and high cost.

Method used

Sprayable thixotropic crosslinkable silicone compositions containing more than 50% aluminum trihydrate as flame retardant and ceramicized filler, silicone thermal stabilizer and ceramicized catalyst are used to provide efficient thermal insulation between the battery cell and module.

Benefits of technology

The composition is ceramicized into an insulating solid at high temperatures, significantly reducing heat flow, thereby effectively protecting the vehicle and the environment during battery pack combustion events, and its economical and ease of application are outstanding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654735A_ABST
    Figure CN119654735A_ABST
Patent Text Reader

Abstract

When a top metal cover of a battery module or battery pack is coated with an addition-curable or moisture-curable ceramizable silicone composition on a side of a cover facing the battery module or individual battery cell, the top metal cover is not coated with a ceramizable silicone composition on a side facing the cover of the battery module or individual battery cell. Metal ion battery modules and battery packs for electric vehicles exhibit substantially reduced heat transfer to areas above the battery modules or battery packs, and an addition-curable or moisture-curable ceramizable silicone composition that is sprayable and thixotropic and contains 50-85% by weight of an aluminum trihydrate-containing filler, the amount is such that the aluminum trihydrate is present in an amount of at least 30 wt% based on the weight of the silicone composition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 419,615, filed on October 26, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to improvements in battery modules suitable for applications requiring large amounts of electrical energy, such as batteries for electric vehicles. Background Art

[0004] In the past, when it was desired to store electrical energy in a rechargeable manner, lead-acid batteries were widely used. However, these batteries have well-known disadvantages. Among these disadvantages are the very high mass and therefore relatively low energy density, the use of lead, which is not environmentally friendly, and the presence of very strong sulfuric acid, which has obvious disadvantages. Nickel-cadmium batteries offer an improvement in storage density, but are relatively expensive. Their use is mainly limited to power tools and consumer electrical products. In addition, the energy storage density of nickel-cadmium batteries is still not as high as desired. Recently, lithium-ion batteries have become ubiquitous due to their higher energy storage capacity and have recently been used to power electric vehicles, which is not possible with lead-acid batteries due to their high weight.

[0005] Lithium-ion batteries used in large-scale applications such as electric vehicles are not produced as individual cells, but as individual cans or "battery cells" that are then assembled into modules. Battery cells can be cylindrical, rectangular, or any specific shape. An electric vehicle "battery" can consist of one or more such modules electrically connected together. Although these modules can be single large modules consisting of multiple individual battery cells, it is currently more common to assemble multiple of these modules to form a "battery pack." These battery packs minimally include a frame, a top cover, and a bottom cover containing the module. Depending on the vehicle design and other characteristics, such as whether the vehicle is a pure electric vehicle, a hybrid electric / gasoline vehicle, an electric aircraft, or an industrial vehicle such as a "hi lo," the battery pack may also contain additional elements, such as reinforcing ribs, etc. A "module" may also consist of a space with a frame or compartment that holds multiple individual battery cells, rather than a self-supporting structure to be assembled into a battery pack.

[0006] Lithium-ion batteries are just one type of modern rechargeable high energy density ion battery that can be used in applications such as those described above. In fact, all of these types of batteries contain active elements, such as lithium, sodium or aluminum, which make these batteries potentially flammable. For example, lithium-ion batteries are known to occasionally catch fire and are therefore prohibited from entering checked baggage when flying. When such batteries are used in electric vehicles, the possibility of a combustion event becomes more likely because these vehicles may be involved in an accident that destroys the integrity of the battery pack or individual battery modules. These types of combustion events are even more dangerous because the water that is usually used to extinguish the fire may actually increase the energy released. Obviously, it is desirable to limit the amount of energy released during a combustion event so that not only the occupants of the vehicle can be protected, but also other combustible parts of the electric vehicle can be protected and prevented from burning. The top and bottom covers of the battery pack provide a degree of protection. However, these covers cannot be made too thick without a significant weight loss, even if thicker covers are possible, because the covers are made of metal, so they will provide little hindrance to heat conduction. While there are many potential insulating materials, such as those based on fumed silica, these fillers are difficult to use in industrial settings and are prone to releasing large amounts of silica particles in the event of an accident. Many other insulating materials are expensive to produce or apply, or cannot withstand the high temperatures that may be encountered. It is therefore desirable to provide an economical means of thermally insulating a vehicle and its surroundings in the event of a battery pack combustion event.

[0007] U.S. Patent 9,507,054 discloses silicon compositions having high optical reflectivity and flame retardant properties, comprising a silicone resin, an organosilicon compound, aluminum hydroxide as a flame retardant (usually present in an amount of up to 45% by weight), and a reflective filler comprising titanium dioxide. These compositions have very high viscosities and are suitable for forming articles by methods such as injection molding, transfer molding, casting, extrusion, overmolding, compression molding, or cavity molding. The high viscosity prevents the economic use of such compounds as thermal insulators in lithium-ion batteries, and relatively low amounts of aluminum hydroxide (also known as aluminum trihydrate or "ATH") do not provide sufficient thermal stability.

[0008] German published application [WA 12106S] discloses compositions that can be ceramized and contain ATH in an amount of up to 65% by weight. However, like the compositions disclosed in the 9,507,054 patent, these compositions have high viscosity and their application is limited to injection molding, casting and compression molding. In addition, in demanding applications, thermal stability may not be high enough, and adding larger amounts of fillers such as ATH only increases viscosity to higher levels, further complicating its use.

[0009] Thixotropic condensation curable compositions are known from U.S. Pat. No. 3,711,570 A. The compositions disclosed in the above patent are typical condensation curable (moisture curable) compositions in which the thixotropy is produced by using emulsion grade polyvinyl chloride particles preferably in an amount of 5 to 50 wt. %. Although such compositions are thixotropic, they are also flammable and can generate toxic hydrogen chloride when burned. Summary of the invention

[0010] Applicants have surprisingly and unexpectedly discovered a sprayable thixotropic crosslinkable silicone composition containing greater than 50% by weight of an inorganic filler containing aluminum trihydrate as a flame retardant and a ceramic filler, a silicone heat stabilizer, and a ceramic catalyst. The total aluminum trihydrate content in the crosslinkable silicone composition is at least 30% by weight. The composition can be economically applied and can provide a high degree of thermal insulation between battery cells and / or modules and lids associated therewith. The crosslinkable silicone composition can be a condensation curable composition or an addition curable composition and can be used as a thermal insulator in battery modules and battery packs for applications requiring high energy storage requirements. The total aluminum trihydrate content in the crosslinkable silicone composition is at least 30% by weight. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 One embodiment of a battery pack is shown in an "exploded" view.

[0012] Figure 2 One embodiment of an assembled battery pack is shown.

[0013] Figure 3 Shows Figure 1 and 2 A cross section of a battery pack showing the ceramizable silicone composition. DETAILED DESCRIPTION

[0014] exist Figure 1 , a generic battery pack is shown in exploded view, wherein the battery pack 1 contains battery modules 2, which contain individual battery "cans" or "cells" 8. The electrical connections do not form part of the present invention and are not shown. The modules are contained within an optional frame 4. The battery pack is enclosed on its upper and lower surfaces by an upper cover 5 and a lower cover 6 secured to each other by fasteners 9. Between the battery modules / cells and the upper cover 5 is disposed a ceramizable silicone composition 7 of the present invention, such as Figure 2 , shown in cross-section in FIG. 1 , in this case shown as having been applied to the lower surface of the upper cover and the upper surface of the lower cover.

[0015] The crosslinkable silicone compositions of the present invention may be condensation curable compositions or addition curable compositions. Condensation curable compositions are compositions that cure in the presence of moisture (generally moisture naturally present in the environment), although added water or moisture may also be utilized to cure or accelerate the curing of these compositions. Addition curable compositions in the sense of the present application are silicone compositions that cure by addition of silicon-bonded hydrogen to ethylenically unsaturated moieties. These compositions require the presence of a hydrosilylation catalyst and are also well known to those skilled in the art.

[0016] Condensation-curable and addition-curable silicone compositions are known for relatively high thermal stability and are even used as baking pans, cupcake "boxes", etc., for use at temperatures up to about 250°C. This upper use temperature makes cross-linked silicone compositions good candidates for use as base polymers for applications requiring high thermal stability. However, when such conventional compositions are highly filled, their mechanical properties suffer, and when such compositions are used as thermal insulators in battery modules, the compositions cannot withstand the high temperatures involved for more than a short period of time. As a result, the temperatures observed on the side of the battery pack cover away from the battery cells or modules quickly reach very high values.

[0017] In the present invention, a highly filled, sprayable, thixotropic and cross-linkable silicone composition is provided, which, when applied to a separate battery cell, module or battery pack as described below, provides a high level of thermal insulation, which greatly reduces the heat flow from the battery cell or module to the area outside the upper cover and / or lower cover. During high energy / high temperature events, the silicone composition ceramicizes into an insulating solid, rather than melting or burning. Despite the high temperature within the battery pack or module, the environment outside the cover does not reach a temperature of 350°C for a considerable period of time (preferably eight to ten minutes or more). The present invention relates to the silicone composition itself, to a battery cell, module and / or battery pack containing the silicone composition of the present invention disposed between the upper cover and / or lower cover of the encapsulated battery cell, module or battery pack, and also to a method for producing battery modules, battery packs and similar structures by spraying a highly filled cross-linkable silicone composition onto a battery cell and / or battery module and curing the silicone composition so that the cured composition is located between the active battery components and the upper cover and / or lower cover.

[0018] Hereinafter, the term "organic silicon composition" refers to the total composition including filler, which is applied by spraying onto components of individual battery cells, battery modules or battery packs. The term "organic silicon component" refers to a compound containing tetravalent silicon, which has hydrogen, hydroxyl, alkoxy and organic groups, preferably alkyl and aryl groups, bonded to silicon atoms. These organosilicon components include, for example, but not limited to, organosilanes, especially alkoxysilanes, and polyorganosiloxanes, commonly referred to as "silicones". The terms "organopolysiloxane" and "polyorganosiloxane" are synonymous in this article, as is the term "silicone". The term "one" with respect to a specific element, component or step means one or more such elements, components or steps, unless otherwise indicated. The term "stopped" is synonymous with the term "terminated" and refers to a specific chemical group or part located at the end of an oligomeric or polymeric polyorganosiloxane chain or chain branch (i.e., in a so-called "M" siloxy unit). The term "thixotropic" is used in its conventional sense, as a composition having a non-Newtonian viscosity whose viscosity decreases with increasing shear rate and becomes higher in the absence of shear. A "sprayable" composition can be applied by spraying or sputtering, as opposed to a composition that requires manual application using a stiff brush or trowel, etc. The term "ion battery" refers to a battery cell, module, etc. that relies on the reversible transformation of a metal from an ionic state to a zero-valent elemental state for the purpose of storing electrical energy, such as, but not limited to, lithium-ion batteries. The addition-curable and moisture-curable silicone compositions described herein are the same compositions used in embodiments involving battery modules and / or battery packs and methods used in the preparation thereof.

[0019] Phrases such as "located between the battery cells and / or modules and the cover" mean that the silicone composition of the present invention is located between the active parts of the battery (e.g., battery cells and / or modules) and the upper cover and / or lower cover, so that the silicone composition can insulate the area above and / or below the module and / or battery pack from the heat generated by one or more defective or damaged batteries. Additional layers or components may be present between the upper cover and / or lower cover and the silicone composition, and / or between the battery cells and / or modules and the silicone composition. In the curable composition, the listed ingredients are those added during the preparation of the composition and are not necessarily consistent with those present after storage. Each of the terms "ATH-containing filler" and "aluminum trihydrate-containing filler" means an inorganic filler in particulate form that contains ATH (aluminum trihydrate) and may also contain additional particulate inorganic fillers. The ATH-containing filler does not include any significant amount of organic fillers such as polymer particles or polymer fibers.

[0020] In one embodiment, the present invention is directed to an electric vehicle battery assembly comprising: an array of a plurality of individual battery cells or modules; optionally but preferably a frame encapsulating the array; a lower cover; an upper cover; and a cross-linked silicone composition disposed between the array of a plurality of batteries or modules and the lower cover and / or the upper cover, the cross-linked silicone composition comprising a sprayable and thixotropic addition-curable or moisture-curable silicone composition comprising at least one polydimethylsiloxane and containing greater than 50% by weight and less than 85% by weight of a filler containing aluminum trihydrate ( The invention relates to a silicone composition comprising a cross-linked silicone composition comprising aluminum trihydrate particles of a filler containing aluminum trihydrate, wherein the aluminum trihydrate particles constitute at least 30 weight percent of the silicone composition), a silicone thermal stabilizer, and at least one additive that promotes ceramicization of the silicone composition when exposed to a temperature of 600°C or higher, wherein the cross-linked silicone composition reduces heat transfer from a side of the silicone composition closest to an array of multiple batteries to an opposite ("outer") side of a lower cover or an upper cover, such that when the cross-linked silicone composition is exposed to a heat source with a temperature greater than 850°C positioned 2.5 cm away from the cross-linked silicone composition, the opposite side of the corresponding cover does not reach a temperature of 350°C for a period of at least two minutes.

[0021] The present invention also relates to an electric vehicle battery assembly as described above, wherein the battery assembly comprises a single module or a plurality of modules, each module containing a second plurality of individual battery cells.

[0022] The present invention further relates to an electric vehicle battery assembly as described above, wherein the sprayable thixotropic silicone composition is an at least two-component addition-curable silicone composition having: a first component, the first component being a vinyl-functional polyorganosiloxane having a viscosity of less than 1000 mPa·s, present in an amount of 20-70 wt % based on the total weight of all organosilicon compounds; optionally, a polyorganosiloxane having a viscosity of less than 10,000 mPa·s, which is optionally silanol-terminated, in an amount of 20-40 wt % based on the total weight of all organosilicon compounds; a silane adhesion promoter; a hydrosilylation catalyst; and optionally, a filler; and a second component containing at least one a Si-H functional crosslinker; optionally, one or more optionally silanol-terminated organopolysiloxanes having a viscosity of less than 10,000 mPa·s; optionally, one or more silane adhesion promoters; and optionally, a filler, wherein at least one component contains a filler comprising aluminum trihydrate, the total amount of filler present in all components is from 50 wt % to 85 wt %, and sufficient aluminum trihydrate is present in the filler to provide at least 30 wt % aluminum trihydrate based on the total weight of all components, wherein at least one component contains a silicone heat stabilizer, at least one component contains a ceramizing promoter for the silicone composition, and wherein at least one of the components contains a silane adhesion promoter.

[0023] In another embodiment of the present invention, the sprayable thixotropic silicone composition is a moisture-curable silicone composition comprising: at least one silanol-terminated polyorganosiloxane having a viscosity of less than 10,000 mPa·s, in an amount greater than 90% by weight based on the total weight of the silicone component of the silicone composition; a silicone heat stabilizer; at least one additive that promotes the ceramization of the silicone composition; optionally, water, preferably in the form of an emulsion, more preferably 0.01-2% by weight of an aqueous silicone emulsion containing about 40% by weight or more of water; and 50-85% by weight of a filler containing aluminum trihydrate, in an amount sufficient to provide at least 30% by weight of aluminum trihydrate based on the total weight of the silicone composition. The moisture-curable silicone composition may consist of only a single "part" or "component", such as a so-called "RTV-1" composition, or may contain multiple components, preferably two components, such as a so-called "RTV-2" composition. The latter is preferred, wherein the water is preferably contained in one of the two components in emulsified form.

[0024] The present invention further relates to a sprayable and thixotropic heat-resistant crosslinkable silicone composition comprising an addition-curable or moisture-curable silicone composition containing: greater than 50 weight percent and less than 85 weight percent of a filler containing aluminum trihydrate, based on the total weight of the curable silicone composition, sufficient to provide at least 30 weight percent of aluminum trihydrate, based on the total weight of the silicone composition, at least one silicone heat stabilizer, and at least one additive to promote ceramization of the silicone composition, wherein the crosslinkable silicone composition, after crosslinking to form a crosslinked silicone, reduces heat transfer from a side of the crosslinked silicone composition opposite a metal substrate to which the crosslinked silicone composition is coated to an opposite side of the metal substrate such that when the side of the crosslinked silicone composition opposite the metal substrate is exposed to a heat source that causes the temperature of the exposed surface of the crosslinked silicone to rise to above 600°C, the opposite side of the metal substrate does not reach a temperature of 350°C or more for a period of at least two minutes.

[0025] The present invention further relates to a sprayable, thixotropic, multi-component, addition-curable silicone composition comprising at least two components. The first component comprises a vinyl-functional polyorganosiloxane having a viscosity of less than 1000 mPa·s in an amount of 20-70 wt % based on the total weight of all silicone components, optionally a polyorganosiloxane having a viscosity of less than 10,000 mPa·s (preferably silanol-terminated) in an amount of less than 30 wt % based on the total weight of all silicone components, a silane adhesion promoter, a hydrosilylation catalyst, and optionally a filler. The second component comprises a Si-H crosslinker, optionally one or more organopolysiloxanes having a viscosity of less than 10,000 mPa·s (preferably silanol-terminated) in an amount preferably less than 30 wt % based on the total weight of all silicone components, optionally a silane adhesion promoter, and optionally a filler. At least one component of the multi-component composition contains a filler, the total amount of filler present in all components being 50 wt % to 85 wt %, sufficient to provide at least 30 wt % of aluminum trihydrate based on the total weight of the silicone composition. At least one component contains a silicone heat stabilizer, at least one component contains a ceramization promoter for the silicone composition at a temperature of 600° C. or higher, and at least one component contains a silane adhesion promoter. The multi-component composition is preferably a two-component composition.

[0026] The present invention also relates to a sprayable thixotropic moisture-curable silicone composition of one or more components, preferably one or two components (RTV-1, RTV-2), which contains a silanol-terminated polyorganosiloxane with a viscosity of less than 10,000 mPa·s in an amount greater than 90 weight percent based on the total weight of the silicone component, an additive that promotes ceramicization of the silicone composition at a temperature of 600° C. or higher, preferably 0.01-2 weight percent of an aqueous silicone emulsion containing a minimum of 40 weight percent water, a silicone heat stabilizer, and 50-85 weight percent of a filler containing aluminum trihydrate, based on the total weight of the silicone composition, which contains sufficient aluminum trihydrate to provide at least 30 weight percent aluminum trihydrate based on the total weight of the silicone composition. The moisture-curable silicone composition, after curing to form a cross-linked silicone composition, reduces heat transfer from a side of the cross-linked silicone composition opposite a metal substrate on which the cross-linked silicone composition is coated to an opposite side of the metal substrate such that when the side of the cross-linked silicone composition opposite the metal substrate is exposed to a heat source having a temperature of 950° C. positioned 2.5 cm from a surface of the cross-linked silicone, the opposite side of the metal substrate does not reach a temperature of 350° C. or greater for a period of at least two minutes.

[0027] The addition-curable silicone composition contains an organopolysiloxane with ethylenically unsaturated moieties, preferably vinyl, ω-alkenyl, alkynyl or allyl moieties, more preferably vinyl moieties, and an organopolysiloxane containing silicon-bonded hydrogen (Si-H "moiety" or "group" or "radical", all synonymous). The addition-curable silicone composition also contains a hydrosilylation catalyst. In such compositions, as is well known to those skilled in the art, it is preferred that no single component contains both ethylenic unsaturation, silicon-bonded hydrogen and a hydrosilylation catalyst. If all three components are present at the same time, premature crosslinking may occur. Although inhibitors can be added to reduce premature crosslinking in one-component compositions, these are only partially successful. Very little crosslinking is required before the viscosity of the composition increases to a level where it is no longer sprayable.

[0028] The polyorganosiloxanes with ethylenically unsaturated moieties are linear or very slightly branched or cyclic organopolysiloxanes which consist mainly of organosiloxy units of formula (1):

[0029] R a SiO (4-a) / 2 (1),

[0030] Where a is 0, 1, 2 or 3, and R is a hydrocarbon or substituted hydrocarbon moiety such as those conventionally used in the art, for example as disclosed in paragraphs

[0023] to

[0025] of U.S. Published Patent Application 2017 / 0283559A1, which is incorporated herein by reference for the present disclosure, preferably an alkyl group having 1-18 carbon atoms, more preferably 1-4 carbon atoms, more preferably methyl; an alkenyl or alkynyl group having 2-18 carbon atoms, preferably 2-8 carbon atoms, wherein the olefinic or acetylenic unsaturation is preferably terminally located away from the silicon atom to which the group is attached, preferably vinyl or allyl, more preferably vinyl; an aryl, alkaryl or aralkyl group of 6-14 carbons, preferably phenyl or phenethyl; or a hydroxyl or alkoxy group, the latter preferably having 1-4 carbon atoms, particularly methoxy or ethoxy. The hydrocarbon group may be substituted with non-interfering substituents such as halogen or cyano, but this is not preferred. In most of the organosiloxy units of formula (1), the unit is a D unit wherein a is 2.

[0031] When linear or slightly branched, the polyorganosiloxane with ethylenically unsaturated moieties is terminated with a so-called M group of formula (2)

[0032] R 1 3SiO 1 / 2 (2)

[0033] Where R 1 Each may be the same or different and has the same meaning as R. 1Preferably, it is selected from methyl or vinyl. The most preferred M terminal units are trimethylsiloxy and vinyldimethylsiloxy units. The most preferred polyorganosiloxane with ethylenically unsaturated moieties is a polydimethylsiloxane with vinyldimethylsiloxy terminal units. Also preferred are polyorganosiloxanes in which the repeating units comprise units of formula (1), wherein one R is an unsaturated hydrocarbon, preferably vinyl, and the other R is a saturated or aromatic hydrocarbon, preferably methyl. In this case, the terminal groups may also contain ethylenically unsaturated groups, or may not contain such groups.

[0034] The polyorganosiloxane with ethylenically unsaturated groups must contain an average of at least two such groups. In addition, the polyorganosiloxane with ethylenically unsaturated groups must have a viscosity of less than 1000 mPa·s and a viscosity such that the entire silicone composition (including fillers) is both thixotropic and sprayable. Thixotropy can be assessed by standard Brookfield viscosity measurements, for example using a rotating cone and plate viscometer, such as those available from AMETEK and BYK-Gardner. Measurements are made at several different shear rates, such as, but not limited to, 0.1 s -1 , 1s -1 , 10s -1 , and optionally, a higher shear rate (e.g. 192 s -1 ) can also establish thixotropic behavior by noting a significantly larger relative increase in viscosity at lower rotational speeds. In the past, it was common to compare the viscosity at 4s -1 and 20s -1 The viscosity measurements at 30° are taken and used to calculate a "thixotropic index". The desired degree of thixotropy may vary somewhat from one cell configuration to another, but is preferably sufficient that when the silicone composition is sprayed onto the desired substrate, it quickly adopts a gel-like or even solid-like configuration. This behavior substantially prevents the silicone composition from flowing downward under gravity, away from its intended application area, until it has had a chance to fully cure. In the latter regard, immediate complete cure is not required.

[0035] The polyorganosiloxane with silicon-bonded hydrogen may be linear, slightly branched or cyclic and should also have a viscosity of preferably less than 1000 mPa·s so that when combined with the other ingredients of the silicone composition, the composition remains sprayable and thixotropic. The polyorganosiloxane with silicon-bonded hydrogen may contain M siloxy units of formula (3):

[0036] R 2 c H (3-c) SiO 1 / 2 (3)

[0037] Where R 2R is a hydrocarbon without ethylenic unsaturation, preferably those described above for R without ethylenic unsaturation, and c is 0, 1, 2 or 3, preferably 1 or 2, most preferably 2.

[0038] The D units present correspond to formula (4):

[0039] R 2 d H (2-d) SiO 2 / 2 (4)

[0040] where d is 0, 1, or 2, and R 2 has the same meaning as in formula (3). The polyorganosiloxane with silicon-bonded hydrogen preferably contains a large number of units of formula (4) in which d is 0 or 1 and units of formula (4) in which d is 2. The straight-chain or slightly branched polyorganosiloxane with silicon-bonded hydrogen may contain silicon-bonded hydrogen only at the chain ends, may contain silicon-bonded hydrogen only along the chain of the polymer, or may contain silicon-bonded hydrogen at two positions. The viscosity of the Si-H functional crosslinker may vary over a wide range, in particular, when the content of silicon-bonded hydrogen is higher, the crosslinker may have a higher viscosity and therefore be present in a smaller amount in the silicone composition at the same ratio of silicon-bonded hydrogen to ethylenic unsaturation. The viscosity is preferably 10,000 mPa·s or less, preferably 5000 mPa·s or less, and most preferably 1000 mPa·s or less. The silicon-bonded hydrogen content may be 0.0002 to 1.7 wt%, preferably 0.05 to 1.2 wt%, more preferably 0.1 to 1 wt%. The silicon-bonded hydrogen-containing crosslinker should be present in conventional amounts, for example to provide 0.1 to 15 silicon-bonded hydrogen atoms per ethylenically unsaturated group, preferably 0.5 to 4 silicon-bonded hydrogen atoms per ethylenically unsaturated group. Higher and lower amounts are also suitable, depending on the other ingredients. The combination of ingredients (including the silicon-bonded hydrogen-containing crosslinker) should be such that the silicone composition is both thixotropic and sprayable.

[0041] The addition-curable silicone composition contains a hydrosilylation catalyst in at least one component. Hydrosilylation catalysts are well known and are typically noble metals or compounds or complexes thereof. The hydrosilylation catalyst is preferably a compound or complex of platinum. Examples of suitable platinum catalysts include any catalysts hitherto used in compositions which can crosslink by adding silicon-bonded hydrogen to aliphatic multiple bonds. Preferably, component (D) comprises a hydrosilylation catalyst from Group 8, 9 or 10 of the Periodic Table of the Elements. Thus, metals and compounds thereof such as platinum, rhodium, palladium, ruthenium and iridium, preferably platinum, can be used. If appropriate, the metal can be fixed on a finely divided support material such as activated carbon, a metal oxide, alumina or silica.

[0042] Preferred hydrosilylation catalysts (D) are platinum and platinum compounds, more preferably platinum compounds soluble in polyorganosiloxane. Soluble platinum compounds include, for example, compounds of the formula (PtCl2.olefin)2 and H (PtCl3. olefins) platinum-olefin complexes, it preferably uses olefins of 2 to 8 carbon atoms, such as isomers of ethylene, propylene, butene and the isomers of octene, or cycloolefins of 5 to 7 carbon atoms, such as cyclopentene, cyclohexene and cycloheptene. Available soluble platinum catalysts further include formula (PtCl2C3H6)2 platinum-cyclopropane complexes, the reaction product of hexachloroplatinic acid and alcohol, ether and aldehyde or its mixture, or the reaction product of hexachloroplatinic acid and methylvinylcyclotetrasiloxane in ethanolic solution in the presence of sodium carbonate. Platinum catalysts with phosphorus, sulfur and amine ligands can be used similarly, and examples are (Ph3P)2PtCl2. Particularly preferably used as component (D) is the complex of platinum and vinylsiloxane, such as symmetrical divinyltetramethyldisiloxane (Karstedt catalyst).

[0043] The amount of the platinum catalyst used should be enough to crosslink the addition curable composition. For example, based on the weight of the organosilicon component, the amount of 0.01ppm to 1000ppm, preferably 0.1ppm to 200ppm, more preferably 20ppm to 120ppm is suitable. If it is necessary to fully cure in a short period of time, a higher amount of catalyst can be used. If it is necessary to slowly cure, a lower amount can be used, or a higher amount can be used in combination with an inhibitor, the inhibitor has for example an acetylenic unsaturated alcohol, such as dehydrogenated linalool, organophosphine, organophosphite and other substances well known to those skilled in the art, for example as disclosed in

[0054] and

[0055] paragraphs of U.S. Publication Application 2008 / 0006179A1, which is incorporated herein by reference. Because the platinum catalyst will also play the role of a ceramic catalyst in the addition curable composition, it may be desirable to use a catalyst slightly higher than the amount used in the addition curable silicon composition that is not designed to be ceramicized at high temperatures, for example 50 to 400ppm, more preferably 50 to 200ppm based on the weight of the organosilicon component. Additionally, since it is generally undesirable to heat ion battery cells, modules or packs to elevated temperatures during manufacturing, it is desirable that the amount of platinum catalyst employed will promote crosslinking at ambient or slightly elevated temperatures below 50°C.

[0044] The organosilicon compound of the moisture-curable silicone composition of the present invention contains a silanol-terminated polyorganosiloxane, an alkoxysilane crosslinker and, if necessary, a condensation catalyst. In order to provide consistent and rapid crosslinking, which may not be possible in an environment with very low relative humidity, it may be desirable to add water to the composition in finely dispersed form, for example in the form of an emulsion with the organopolysiloxane, so it is necessary to use a two-component composition in which the water is contained in a component supplied just before or during spraying of the composition, or in a component that does not contain a crosslinker. Like the addition-curable composition of the present invention, the moisture-curable composition is thixotropic and sprayable, and ceramizes at elevated temperatures due to the additional presence of a ceramizing catalyst.

[0045] The silanol-terminated polyorganosiloxane of the moisture-curable silicone composition is a linear or very lightly branched or cyclic organopolysiloxane consisting primarily of organosiloxy units of formula (4):

[0046] R 2 e SiO (4-e) / 2 ,

[0047] wherein e is 0, 1, 2 or 3, preferably 2, and R 2 is a hydrocarbon or substituted hydrocarbon moiety such as those conventionally used in the art, for example as previously described, preferably an alkyl group having 1 to 18 carbon atoms, more preferably 1 to 4 carbon atoms, more preferably methyl; an alkenyl or alkynyl group having 2 to 18 carbon atoms, preferably 2 to 8 carbon atoms, although these are not necessary or preferred, and when present, preferably vinyl or allyl, more preferably vinyl; an aryl, alkaryl or aralkyl group of 6 to 14 carbon atoms, preferably phenyl or phenethyl; or a hydroxyl or alkoxy group, the latter preferably having 1 to 4 carbon atoms, especially methoxy or ethoxy. At least two hydroxyl groups are present. The hydroxyl and alkoxy groups are preferably present in the terminal M group together with one or two hydrocarbon groups as described above, wherein e is 3. The terminal silanol group constitutes the "silanol-terminated" requirement of the silanol-terminated polyorganosiloxane. The hydrocarbon group may be substituted with non-interfering substituents such as halogen or cyano, but this is not preferred. In most organosiloxy units of formula (4), the unit is a D unit, wherein e is 2. The preferred silanol-terminated polyorganosiloxane is a linear polydimethylsiloxane having dimethylsilanol terminal groups. Preferably, the silanol-terminated polyorganosiloxane contains hydrocarbon groups which are exclusively alkyl groups, preferably alkyl groups containing 1 to 4 carbon atoms, more preferably methyl or phenyl, most preferably methyl.

[0048] The silanol-terminated polyorganosiloxane has a viscosity of less than or equal to 10,000 mPa·s, more preferably less than or equal to 5000 mPa·s, even more preferably less than or equal to 2000 mPa·s, and most preferably less than or equal to 1000 mPa·s at 25°C. The amount and viscosity of the silanol-terminated polyorganosiloxane are selected so that the silicone composition is thixotropic and sprayable. Higher viscosity silanol-terminated polyorganosiloxanes can also be used in combination with low viscosity silanol-terminated polyorganosiloxanes as long as the thixotropy and sprayability requirements are met.

[0049] The moisture-curable composition contains a crosslinking agent. Crosslinking agents for moisture-curable compositions are well known to those skilled in the art and include alkoxysilanes, acetoxysilanes, oxime silanes and partial hydrolysis thereof. Alkoxysilanes are preferred due to the environmental tolerance of their volatile hydrolysis products (especially methanol and ethanol) compared to, for example, acetic acid in the case of acetoxysilane. Suitable crosslinking agents are C 1-4 Alkoxy, preferably methoxy or ethoxy, most preferably methoxy silane. Examples include tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane. For example, silanes with C 1-4 Alkoxy (preferably methoxy) and aminoalkyl (such as aminoethyl, aminopropyl, aminoethylaminopropyl and aminopropylaminoethyl) crosslinking agents are suitable and are used not only as crosslinking agents, but also as cocatalysts and adhesion promoters in moisture-curable compositions. Poly (aminoalkyl) functional alkoxysilanes are also suitable. Examples of acetoxysilane crosslinking agents are methyl triacetoxysilane, ethyl triacetoxysilane and propyl triacetoxysilane.

[0050] A condensation catalyst is generally required. Such condensation catalysts are well known and include, for example, bismuth compounds, titanates, and certain tin compounds such as tin(II) acetate, tin(II) octoate, and tin(II) laurate. Other suitable condensation catalysts can be readily identified from the patent and scientific literature. If the moisture-curable silicone composition is extremely reactive, the presence of a condensation catalyst can be avoided, or its amount can be limited to very low concentrations. When a condensation catalyst is present, its amount is generally 0.005 to 2 weight percent, preferably 0.01 to 1 weight percent, more preferably 0.02 to 0.2 weight percent, based on the total weight of the silicone component.

[0051] Aqueous emulsions or water itself can be used to accelerate the curing of the wet curable composition. When aqueous emulsions or water are used, they are added as a separate composition or added to a component that does not contain a condensable polyorganosiloxane, a crosslinking agent, and a condensation catalyst at the same time. The aqueous emulsion or water is conveniently mixed into the remaining crosslinkable composition, i.e., in the component before the spray head or in the component included as an integral component of the spray head itself, by using a mechanical or static mixer just before spraying or during spray application. The actual components that are replaced by mixing are not very important, except that mixing should not be carried out sufficiently before spraying so that the composition does not start to cure prematurely and develop to a viscosity that is no longer sprayable.

[0052] The moisture curing composition is most preferably a two-component composition, wherein the first component contains a silanol-terminated base polymer and emulsified water, and the second component contains a crosslinker and a catalyst. The second component containing the crosslinker generally also contains a condensation catalyst and a functional or non-functional polyorganosiloxane, the latter being present so that the second component can be used in larger amounts than the crosslinker alone to facilitate accurate metering, and may also contain aminoalkyl functional silanes, such as aminoalkyl alkoxy silanes. Crosslinkers and multi-component crosslinker compositions are commercially available or can be readily formulated by those skilled in the art. The amount of the second component to be mixed into the first component depends essentially on the weight percentage of the crosslinker contained in the second component, and the second component can be formulated to provide a volume mixing ratio of the first component to the second component that can vary over a wide range, for example from 1:2 to 20:1, preferably from 1:1 to 15:1. A suitable crosslinker is Wacker Catalyst T 77, which is particularly recommended for use in a volume ratio of 8:1 to 12:1. The crosslinker contains about 20-25 wt % 1,2-bis(triethoxysilyl)ethane, 10-15 wt % aminoalkylalkoxysilane, 5-10 wt % carbon black, polydimethylsiloxane and 0.3-1.0 wt % tin catalyst. Since a relatively small portion of the second component is used relative to the first component, the second component can be in the form of a highly viscous or even pasty composition before mixing with the first component. Therefore, the second component can use polyorganosiloxanes, including silanol-terminated polyorganosiloxanes, which have a much higher molecular weight than that recommended for use in the first component. However, when the second component is used in a large ratio (e.g., 1:1 or 2:1), the second component must also have a relatively low viscosity so that the composition remains sprayable. In compositions where the second component is present in a relatively large amount, the pot life and curing time are shortened. However, the final pot life and curing time are not only a function of the second component, but also depend significantly on the composition of the first component, including the amount of silanol-terminated polymer and whether emulsified water is present. In the case of manufacturing battery modules and / or battery packs, a very fast curing rate is generally desired in order to reduce the assembly time of each module or each battery pack as much as possible.

[0053] There are several components that are common to both addition-curable silicone compositions and moisture-curable silicone compositions or that are optional in both compositions. These components include: ATH-containing fillers, which are required in both types of compositions; adhesion promoters, which are required in addition-curable compositions but may also be present in moisture-curable compositions in addition to the alkoxysilane crosslinkers that are also present, and which may also improve the organic / inorganic interface; low viscosity polyorganosiloxane diluents, which are optional in both compositions to reduce viscosity and enhance sprayability; biocides, which are optional components in both compositions to combat microbial growth during storage; stabilizers, which are used in both types of compositions to stabilize the silicone component against exposure to elevated temperatures; and organic solvents, which are not preferred and are preferably absent but may be used to reduce system viscosity.

[0054] The ATH-containing filler is an integral part of the composition of the present invention. The ATH-containing filler is present in both compositions in an amount of 50-85 wt. %, based on the total weight of the sprayable thixotropic silicone composition. The ATH portion of the ATH-containing filler must be sufficient to provide at least 30 wt. %, preferably at least 40 wt. %, more preferably at least 50 wt. %, even more preferably at least 60 wt. %, still more preferably at least 70 wt. %, and most preferably at least 80 wt. % of ATH, based on the total weight of the silicone composition. Most preferably, the entire ATH-containing filler consists only of ATH.

[0055] Aluminum trihydrate (ATH) is in particulate form and has an average particle size of less than 300 μm, preferably less than 200 μm, and most preferably less than 100 μm. The average particle size is preferably greater than 10 μm, more preferably greater than 20 μm. ATH has a particle size of less than 20 μm. 2 / g, more preferably less than 10m 2 / g and preferably greater than 0.5m 2 / g, more preferably greater than 0.8m 2 ATH is available from many sources around the world, including RJ Marshall Company, Huber, etc.

[0056] The ATH may be untreated, or it may be hydrophobized. The use of a hydrophobized ATH has been found to be effective in reducing viscosity so that the silicone composition is flowable and preferably sprayable. The ATH may be provided in an already hydrophobized form, or may be hydrophobized in situ, for example by including a reactive polyorganosiloxane or silane that will react with the surface hydroxyl groups after addition to the silicone composition. The ATH may also be hydrophobized by coating with natural or synthetic waxes, fatty acids, fatty acid salts, fatty acid esters, and other similar hydrophobic compounds well known to those skilled in the art. Preferred hydrophobic ATHs are SB36SG, which has an aluminum hydroxide content of about 99.6% by weight, an average particle size of about 36 μm, and a particle size of 1.0 μm. 2 / g BET surface area, available from Huber.

[0057] Fillers other than ATH present in the sprayable thixotropic silicone composition include metal carbonates such as magnesium carbonate and calcium carbonate, magnesium hydroxide, silicon dioxide, titanium dioxide and other insoluble or poorly soluble metal oxides. Regarding such fillers, it is important to evaluate the effect of the filler on the thermal properties of the cured silicone composition and the effect of the filler on the viscosity and thixotropy of the silicone composition. It is preferred to avoid fillers with relatively high costs, such as titanium dioxide. Fillers such as carbonates can be synthetic carbonates or natural carbonates, such as those derived from limestone, marble or dolomite. Some fillers, such as zinc oxide, can be added in small amounts to increase the thixotropic properties of the composition. Mica, asbestos, talc, wollastonite and other naturally occurring fillers in expanded or non-expanded form are also suitable. The same applies to pyrolytic fillers such as pyrolytic silica and pyrolytic titanium dioxide, which can be obtained in very small particle sizes with corresponding high BET surface areas. Preferably, however, the BET surface area of ​​the additional filler, particularly when used in amounts greater than about 3 weight percent based on the total weight of the silicone composition, should be of the same general size and BET surface area as in the case of the ATH particles discussed previously. The additional filler can be used as prepared, i.e., non-hydrophobic, can be provided as a hydrophobic filler by appropriate surface modification, or can be hydrophobized in situ. Inorganic fillers in the form of microspheres can also be used. Such microspheres are typically composed of glass or ceramic materials and preferably have a particle size in the same range as the ATH filler. As with other non-ATH fillers, inorganic microspheres are commercially available from a number of sources. Filler density is also a consideration when selecting a non-ATH filler, when used in amounts greater than 10 weight percent based on the total weight of the silicone composition.

[0058] The amount of non-ATH filler can range from 0.0 wt% to about 55 wt%, with 55 wt% being the preferred upper limit, preferably greater than 0.0 to about 20 wt%, and more preferably greater than 0.0 to about 10 wt%. Too much non-ATH filler may result in reduced thermal properties.

[0059] Both the addition-curable silicone composition and the wet-curable silicone composition contain a ceramicizing catalyst that promotes the conversion of the silicone composition into a porous ceramic material at high temperatures, preferably at 600°C or higher, for example at temperatures around 800°C to 900°C. The composition of the ceramicizing catalyst can vary as long as ceramicization is achieved. However, the ceramicizing catalyst is preferably a platinum compound, such as those previously disclosed in paragraphs

[0034] and

[0035] . In the addition-curable silicone composition of the present invention, the platinum hydrosilylation catalyst plays the dual role of catalyzing the curing of the silicone composition by hydrosilylation crosslinking, and since the platinum catalyst is not removed but retained in the composition, it also serves as a ceramicizing catalyst. In the wet-curable composition, it is necessary to add a ceramicizing catalyst because the wet-curable composition does not require a platinum catalyst for crosslinking. In the case of the wet-curable composition, the same platinum catalyst as described above can be used in the aforementioned amount.

[0060] Both the addition-curable silicone composition and the moisture-curable silicone composition contain a heat stabilizer for the silicone. The heat stabilizer is present in a small amount, for example, 0.1 wt % to 3 wt %, preferably 0.5 wt % to 2 wt %, more preferably 0.5 to 1.8 wt %, most preferably 0.5 to 1 wt %, based on the total weight of the silicone composition. A suitable heat stabilizer is particulate titanium dioxide, preferably provided as a dispersion in a polyorganosiloxane. The amount of titanium dioxide is insufficient to make the composition reflective, and this is particularly true when an inorganic dark pigment such as black pigment iron oxide is also present. Silicone heat stabilizers extend the upper use temperature of the silicone.

[0061] Inorganic pigments are optional components in addition-curable silicone compositions and moisture-curable silicone compositions. In principle, organic pigments should be avoided because they are generally flammable. Suitable inorganic pigments are particularly metal oxides of metals other than titanium, such as iron oxide. Pigment iron oxides can be obtained in various colors from yellow to red to black. Black iron oxide pigments are particularly suitable. Based on the total weight of the silicone composition, these pigments are provided in an amount of 0.1% to 5% by weight, preferably 0.5 to 4% by weight, and most preferably 0.8 to 2% by weight, based on a 20% by weight dispersion of a pigment in an organopolysiloxane, preferably a vinyl functional organopolysiloxane. A suitable pigment dispersion is SILCOPAS220black available from Avient.

[0062] Both addition-curable silicone compositions and moisture-curable silicone compositions may contain adhesion promoters. In moisture-curable compositions, alkoxysilane crosslinkers may be used as adhesion promoters. However, since alkoxysilanes are not essential components in addition-curable compositions, it may be necessary to add them as adhesion promoters in these compositions, or to add a separate adhesion promoter in either type of composition. These adhesion promoters preferably contain reactive and / or polar groups such as glycidyl, acryl, aminoalkyl, and the like. Examples include GENIOSIL GF 80, (3-glycidyloxypropyltrimethoxysilane), MAPTMO silane (N-methyl-3-aminopropyltrimethoxysilane), GENIOSIL GF91 (N-(2-aminoethyl)-3-aminopropyltrimethoxysilane), methacryloxypropyltrimethoxysilane, acetoxysilane, and the like. Partial hydrolyzates of these silane adhesion promoters may also be used. When present as a separate component, the adhesion promoter is preferably present in an amount of 0.1 to 5 wt %, more preferably 0.2 to 4 wt %, still more preferably 0.2 to 3 wt %, based on the total weight of the silicone composition.

[0063] The materials for the upper and lower covers, frames and other parts of the battery module and / or battery pack are conventional and, in order to reduce flammability, are usually made of metal, such as conventional steel, stainless steel or aluminum. For cost reasons, stainless steel is not preferred. For reasons of reducing vehicle weight, aluminum is most preferred. In modern motor vehicle components, many metal parts are painted or otherwise coated to provide corrosion resistance in particular. Electrophoretic coating processes are usually used. Although such coatings are particularly useful in preventing corrosion, when using such coatings, care must be taken to assess the effect of the coating on the thermal properties of the battery module and / or battery pack. For example, but not limited to, it has been found that certain electrophoretic coatings significantly reduce the heat resistance provided by the silicone composition of the present invention. Therefore, when testing thermal conductivity, it is important to use the actual material that will be used in production. It has been particularly found that non-electrophoretically coated aluminum covers are particularly suitable for extending the time for the exposed surface of the cover to reach an unacceptable temperature. The top and bottom (outer) surfaces of the electrophoretically coated top and bottom covers are generally free of problems.

[0064] The silicone composition is sprayable due to being a relatively low viscosity fluid at reasonable shear amounts. These properties also allow for coating methods that are unique to flowable compositions, such as blade coating, spin coating, and the like. However, since many components of the battery module and / or battery pack are non-planar and therefore not suitable for these application methods, it is highly preferred that the composition is sprayable. In order to be sprayable, the viscosity must be relatively low under the shear experienced in the nozzle. In this regard, directional spraying produced by impinging the silicone composition onto a rotating disk or the like can be used, but conventional spraying equipment is preferably used. Such equipment is capable of easily spraying compositions having a viscosity of up to about 30,000 mPa·s or slightly higher. When the viscosity exceeds about 20,000 mPa·s, although spraying is possible, it becomes difficult. Due to the large content of filler in the silicone composition of the present invention, it is very surprising that the composition is sprayable. The viscosity of the silicone composition at low shear levels is quite high, for example at 0.5s -1 The viscosity of the applied coating is preferably up to 35,000 mPa·s or more at room temperature, and even higher at rest. However, since the compositions are thixotropic, i.e. shear thinning, they can still be sprayed effectively. To further increase the sprayability, or to allow the spraying of more viscous compositions, the spraying equipment can be equipped with an ultrasonic transducer to reduce the local viscosity near the spray head. High-pressure and low-pressure sprayers can be used with or without an air or other gas flow. Prior to curing, the thickness of the applied coating is preferably between 0.2 and 5 mm, more preferably between 0.5 and 2.5 mm. The thickness of the coating after curing is substantially the same as the thickness before curing. Preferably, after 200s -1 The viscosity at RT is less than 10,000 mPa·s, more preferably less than 7000 mPa·s, still more preferably less than 5000 mPa·s, and most preferably less than 4000 mPa·s.

[0065] Preferably, the silicone composition is sprayed onto the underside of the top cover of the battery module and / or battery pack, which is preferably an aluminum sheet. The sprayed silicone composition begins to cure immediately and can be significantly or completely cured before the cover is assembled to the remaining battery components, or the cover and applied silicone composition can be placed on the remaining components while in a very low state of cure. In the case where the curing silicone composition is still tacky on its surface, applying the cover to the remaining components before complete cure can enhance the mechanical strength of the battery module and / or battery pack.

[0066] The invention will now be illustrated by the following non-limiting examples. The viscosity of the composition is measured at room temperature or 25°C and can be evaluated, for example, as disclosed in ISO 3219. Based on the following examples and the foregoing discussion, a person of ordinary skill in the art will be able to produce various compositions that are flowable, preferably sprayable and thixotropic, contain a desired amount of ATH-containing filler, and are suitable for producing insulators for metal ion batteries. All parts described herein are parts by mass. All percentages described herein are percentages by mass.

[0067] Example 1

[0068] The addition-curable silicone composition is prepared as a two-component composition.

[0069] Prepare the first component by mixing: 4 parts of GF 80; 1 part of MAPTMO silane; 24 parts of VIPO 120, a vinyl functional polymer available from Wacker Chemie having a viscosity of 120 mPa·s; 5.2 parts of SILCOPAS 220, a dispersion of Fe3O4 iron oxide in a vinyl functional polyorganosiloxane; 0.8 parts of POLYMER VI-P-5, an oligovinyl functional polyorganosiloxane having an average of about 3 vinyl groups per molecule, available from Wacker Chemie; 0.8 parts of CATALYST EP, a platinum catalyst in a vinyl functional polydimethylsiloxane, available from Wacker Chemie; 130 parts of Huber SB-36SG ATH; 4 parts of a silicone heat stabilizer comprising about 34 weight percent titanium dioxide dispersed in 40 weight percent of a vinyl functional organopolysiloxane having a viscosity of about 1100 mPa·s, and also comprising a small amount of a platinum catalyst solution and GF 91; 3 parts of hexadecyltrimethoxysilane; and 10 parts of a silanol-terminated polydimethylsiloxane having a viscosity of about 1000 mPa·s.

[0070] The second component is prepared by mixing 8 parts of a Si-H functional polydimethylsiloxane crosslinker containing 0.77 wt. % silicon-bonded hydrogen; 3 parts of GENIOSIL GF 80; 1 part of MAPTMO silane; 9.8 parts of a Si-H functional polydimethylsiloxane crosslinker containing about 0.15 wt. % silicon-bonded hydrogen; 12 parts of VIPO 120, a vinyl functional polyorganosiloxane having a viscosity of about 120 mPa·s; 130 parts of Huber SB-36SG ATH; 3 parts of hexadecyltrimethoxysilane; 10 parts of a silanol terminated polydimethylsiloxane having a viscosity of about 1000 mPa·s; and 4 parts of the silicone heat stabilizer used in the first component.

[0071] The two components were supplied separately to a static mixer just before the spray head and sprayed onto a 0.6 mm aluminum substrate at a thickness of about 4 mm. The coated sheet was fixed in a vertical position by a welder's fixture and a propane burner with a flame temperature in the range of 850-1000°C was positioned 2.5 cm from the silicone surface. The temperature on the opposite side of the sheet was measured using a FLIR autofocus thermal imaging camera, which can be used to measure temperatures in the range of 0-650°C with an accuracy of about ±2°C. The outside of the panel did not reach 350°C even after 8 minutes, while a similar panel composed of electrophoretically coated steel without the silicone composition deposited thereon reached this temperature in less than 10 seconds. Inspection of the silicone coating after this exposure to high temperatures above 600°C showed the presence of a black porous ceramic material. The silicone composition provides unexpectedly effective thermal insulation at the high temperatures involved.

[0072] Example 2

[0073] A moisture-curable first component was prepared by mixing: 6.3 parts by weight of the silicone heat stabilizer used in Example 1; 255.5 parts of ATH, 0.85 parts of an emulsion of about 35 weight percent water dispersed in silicone, and 115.6 parts of a silanol-terminated polydimethylsiloxane having a viscosity of about 1000 mPa·s. The second component was Wacker Catalyst T 77 available from Wacker Chemie, used in a 10:1 ratio of first component to second component. The mixed components were sprayable and were sprayed onto the panel in a manner similar to Example 1. When subjected to the same flame test as used in Example 1, the opposite side of the panel did not reach 350°C for more than 8 minutes.

[0074] The first component (without catalyst) was measured at room temperature viscosity at 0.5s -1 The shear rate is 38,000 mPa·s at 5 s -1 15,000 mPa·s at 10 s -1 13,700 mPa·s at 192s -1 The second component has a 0.5s of about 200,000 mPa·s. -1 Viscosity. The viscosity of the mixed first and second components measured shortly after mixing at 0.5s -1 The shear rate is 43,600 mPa·s at 5 s -1 15,500 mPa·s at 10 s -1 13,800 mPa·s at 192s -1Note the very high viscosity at low shear rates, which is 6160 mPa·s at 192 s -1 The shear rate decreases by about 6 times.

Claims

1. An electric vehicle battery assembly, comprising: a) an array of multiple individual metal ion batteries; b) optionally, a frame laterally surrounding said array of said plurality of individual metal ion batteries; c) optionally, a lower cover; d) the upper cover; and e) a cross-linked, sprayable, thixotropic, addition-curable or moisture-curable silicone composition disposed between an array of a plurality of cells and at least one of the lower and / or upper covers, the addition-curable or moisture-curable silicone composition comprising: greater than 50 wt % and less than 85 wt % of a filler containing aluminum trihydrate, based on the total weight of the curable silicone composition, the aluminum trihydrate particles of the filler constituting at least 30 wt % of the curable silicone composition; and at least one ceramicizing additive that promotes ceramicization of the cross-linked silicone composition when exposed to a temperature of 600° C. or greater, wherein the cross-linked silicone composition reduces heat transfer from a surface of the cross-linked silicone composition closest to the array of multiple batteries to an outer surface of the lower cover or the upper cover carrying the cross-linked silicone composition, such that when the surface of the cross-linked silicone composition closest to the array of multiple batteries is exposed to a heat source with a temperature greater than 850°C positioned 2.5 cm from the surface of the silicone composition, the outer surface does not reach a temperature of 350°C for a period of at least two minutes.

2. The electric vehicle battery assembly of claim 1, wherein the array of a plurality of individual cells is in the form of battery modules, each module containing a second plurality of individual cells, and the silicone composition is applied to a top cover of the battery assembly.

3. The electric vehicle battery assembly of claim 1, wherein the sprayable thixotropic silicone composition is at least a two-component addition-curable silicone composition comprising: a) a first component comprising: i) at least one vinyl-functional polyorganosiloxane having a viscosity of less than 4000 mPa·s, preferably less than 1000 mPa·s, in an amount of 20 to 70% by weight, based on the total weight of all organosilicon compounds; ii) optionally, one or more silanol-terminated polyorganosiloxanes or non-functional polyorganosilanes having a viscosity of less than 10,000 mPa·s, preferably less than 1000 mPa·s, in an amount of 20-40 wt % based on the total weight of all organosilicon compounds; iii) at least one silane adhesion promoter; iv) at least one hydrosilylation catalyst; v) optionally, a filler; and b) a second component comprising: i) at least one Si-H functional crosslinking agent; ii) optionally one or more silanol-terminated organopolysiloxanes or non-functional polyorganosiloxanes having a viscosity of less than 10,000 mPa·s, preferably less than 1000 mPa·s; iii) optionally, one or more silane adhesion promoters; iv) optionally, a filler, wherein at least one of the first and second components contains: a filler containing aluminum trihydrate, the total amount of filler present in all components being 50 wt % to 85 wt %, and the aluminum trihydrate being present in the filler in an amount sufficient to provide at least 30 wt % aluminum trihydrate, preferably at least 50 wt % aluminum trihydrate, more preferably at least 70 wt % aluminum trihydrate, and most preferably at least 80 wt % aluminum trihydrate based on the total weight of all components; a silicone heat stabilizer; and wherein at least one of the components contains the ceramizing additive, preferably a ceramizing additive containing platinum; and wherein at least one of the components contains a silane adhesion promoter.

4. The electric vehicle battery assembly of claim 1 or 3, further comprising up to 5 wt% of a thermal stabilizer composition comprising titanium dioxide.

5. The electric vehicle battery assembly of claim 1 or 2, wherein the sprayable thixotropic silicone composition is a moisture-curable silicone composition comprising: i) at least one silanol-terminated polyorganosiloxane having a viscosity of less than 10,000 mPa·s in an amount greater than 90 wt % based on the total weight of the organosilicon component; ii) at least one ceramizing additive that promotes ceramizing of the organosilicon composition; iii) optionally 0.01-2 wt. % of an emulsion of water and silicone; iv) at least one alkoxysilane crosslinker; v) optionally, an adhesion promoter different from component iv); and iv) 50-85 wt. % of an aluminum trihydrate-containing filler in an amount sufficient to provide at least 30 wt. % aluminum trihydrate based on the total weight of the silicone composition, and v) at least one thermal stabilizer.

6. The electric vehicle battery assembly of claim 5, wherein the moisture-curable silicone composition is at least a two-component composition, one component comprising an emulsion of water and silicone and a silanol-terminated organopolysiloxane, and a second component comprising an alkoxysilane crosslinker.

7. The electric vehicle battery assembly of claim 5, wherein the silicone heat stabilizer comprises titanium dioxide in an amount sufficient to provide 0.1 to 3 wt% titanium dioxide, preferably 0.2 wt% to less than 2 wt% titanium dioxide, based on the total weight of the silicone composition.

8. A heat-resistant cross-linkable silicone composition useful for making the metal ion vehicle battery assembly of claim 1, said composition being sprayable and thixotropic, comprising: An addition-curable or moisture-curable silicone composition comprising: greater than 50 wt % and less than 85 wt % of a filler containing aluminum trihydrate, based on the total weight of the curable silicone composition, and sufficient to provide at least 30 wt % aluminum trihydrate, preferably at least 50 wt % aluminum trihydrate, more preferably at least 70 wt % aluminum trihydrate, and most preferably at least 80 wt % aluminum trihydrate, based on the total weight of all of the silicone composition; a silicone heat stabilizer; and at least one ceramizing additive that promotes ceramizing of the silicone composition, wherein the curable silicone composition, after crosslinking to form a crosslinked silicone, reduces heat transfer from a side of a metal substrate on which the crosslinked silicone composition is coated to an opposite side of the metal substrate such that when the side of the crosslinked silicone composition opposite the metal substrate is exposed to a heat source that causes the temperature of the surface of the crosslinked silicone to rise in excess of 600° C., the opposite side of the metal substrate does not reach a temperature of 350° C. or greater for a period of at least two minutes.

9. The heat-resistant crosslinkable silicone composition according to claim 8, which is a sprayable thixotropic multi-component addition-curable silicone composition comprising at least two components: a) a first component comprising: i) at least one vinyl-functional polyorganosiloxane having a viscosity of less than 4000 mPa·s, preferably less than 1000 mPa·s, in an amount of 20 to 70% by weight, based on the total weight of all silicone components; ii) optionally, at least one silanol-terminated polyorganosiloxane or non-functional polyorganosilane having a viscosity of less than 10,000 mPa·s, preferably less than 1000 mPa·s, in an amount of less than 30 wt. % based on the total weight of all organosilicon compounds; iii) optionally, a silane adhesion promoter; iv) at least one hydrosilylation catalyst; v) optionally, a filler; and b) a second component comprising: i) at least one Si—H crosslinking agent; ii) optionally, one or more silanol-terminated organopolysiloxanes or non-functional organopolysiloxanes having a viscosity of less than 10,000 mPa·s, preferably less than 1000 mPa·s, in an amount of less than 30 wt % based on the total weight of all organosilicon components; iii) optionally, one or more silane adhesion promoters; iv) optionally, a filler, wherein at least one component contains a filler containing aluminum trihydrate, the total amount of aluminum trihydrate-containing filler present in all components is 50 wt % to 85 wt % and is sufficient to provide at least 30 wt % aluminum trihydrate, preferably at least 50 wt % aluminum trihydrate, more preferably at least 70 wt % aluminum trihydrate, and most preferably at least 80 wt % aluminum trihydrate based on the total weight of the curable silicone composition; at least one component contains a ceramicizing additive that promotes ceramicization of silicone at temperatures of 600° C. or higher, at least one component comprises a silicone heat stabilizer containing titanium dioxide, and at least one component contains a silane adhesion promoter.

10. A sprayable thixotropic moisture-curable silicone composition suitable for use in making the metal ion vehicle battery assembly of claim 1, comprising: i) at least one silanol-terminated polyorganosiloxane having a viscosity of less than 10,000 mPa·s, preferably less than 1000 mPa·s, in an amount greater than 90 wt % based on the total weight of the silicone component of the silicone composition; ii) silicone heat stabilizer; and iii) at least one ceramizing additive that promotes ceramizing of the silicone composition at a temperature of 600° C. or higher; iv) optionally, 0.01-2 wt. % of an emulsion of silicone and water; v) 50-85 wt % of an aluminum trihydrate-containing filler, based on the total weight of the silicone composition, containing sufficient aluminum trihydrate to provide at least 30 wt % aluminum trihydrate, preferably at least 50 wt % aluminum trihydrate, more preferably at least 70 wt % aluminum trihydrate, and most preferably at least 80 wt % aluminum trihydrate, based on the total weight of the silicone composition, wherein the moisture-curable silicone composition, after curing to form a cross-linked silicone composition, reduces heat transfer from a side of a metal substrate on which the cross-linked silicone composition is coated to an opposite side of the metal substrate such that when the side of the cross-linked silicone composition opposite the metal substrate is exposed to a heat source having a temperature of 850° C. positioned 2.5 cm from the surface of the cross-linked silicone, the opposite side of the metal substrate does not reach a temperature of 350° C. or greater for a period of at least 2 minutes, preferably at least 5 minutes, and more preferably at least 8 minutes.

11. The moisture-curable silicone composition of claim 10, wherein the moisture-curable silicone composition is at least a two-component composition, one component comprising an emulsion of water in silicone and a silanol-terminated organopolysiloxane, and a second component comprising an alkoxysilane crosslinker and a condensation catalyst.

12. The silicone composition of claim 9 or 10, wherein the silicone heat stabilizer comprises titanium dioxide in an amount sufficient to provide 0.1 to 3 wt% titanium dioxide, preferably 0.2 wt% to less than 2 wt% titanium dioxide, based on the total weight of the silicone composition.

13. A method for manufacturing a metal ion battery module and / or battery pack according to claim 1 or 2, comprising: a) assembling a plurality of individual metal ion battery cells into a battery module, and optionally assembling a plurality of said battery modules into a battery pack; b) providing at least a top metal cover sized to enclose at least a top surface of the battery module and / or battery pack, and optionally, a bottom metal cover sized to enclose at least a bottom surface of the battery module and / or battery pack; c) applying a flowable and preferably sprayable thixotropic crosslinkable silicone composition to at least the top metal cover, the crosslinkable silicone composition comprising: an addition-curable silicone component or a moisture-curable silicone component and an aluminum trihydrate-containing filler in an amount of 50-85 wt. %, based on the total weight of the silicone composition, the amount of the aluminum trihydrate-containing filler and the aluminum trihydrate ratio of the aluminum trihydrate-containing filler being such as to provide at least 30 wt. % aluminum trihydrate, more preferably at least 50 wt. % aluminum trihydrate, still more preferably at least 70 wt. % aluminum trihydrate, most preferably at least 80 wt. % aluminum trihydrate; and further comprising a silicone heat stabilizer and at least one ceramizing additive; d) installing the top metal cover over the plurality of metal ion battery cells or battery modules, wherein the cross-linkable silicone composition, after cross-linking to form a cross-linked silicone, reduces heat transfer from a side of the metal substrate on which the cross-linked silicone composition is coated to an opposite side of the metal substrate such that when the side of the cross-linked silicone composition opposite the metal substrate is exposed to a heat source that causes the temperature of the cross-linked silicone to rise in excess of 600° C., the opposite side of the metal substrate does not reach a temperature of 350° C. or greater for a period of at least two minutes.

14. An ion battery module or battery pack prepared by the method according to claim 13.

Citation Information

Patent Citations

  • Curable organopolysiloxane compositions

    US20080006179A1

  • Organopolysiloxane compositions which can be crosslinked by means of a condensation reaction

    US20170283559A1

  • Organopolysiloxane-polyvinyl chloride blends

    US3711570A

  • Composition for forming an article having excellent reflectance and flame retardant properties and article formed therefrom

    US9507054B2